Pemanfaatan Media Grafis dalam Layanan Informasi Dampak Pelanggaran Disiplin untuk Meningkatkan Perilaku Disiplin Siswa di Sekolah - Muh Mansyur Thalib; Ridwan Syahran; Azam Arifyadi (Indonesian Journal of Educational Counseling, 2019)
UTILIZATION OF GRAPHIC MEDIA IN INFORMATION SERVICES THE IMPACT OF DISCIPLINE VIOLATION TO IMPROVE DISCIPLINE BEHAVIOR OF STUDENTS IN SCHOOL. This study aimed to determine the effect of the use of visual media in information services on the impact of disciplinary violations on improving student discipline behavior. This study uses 90 students as subjects (30 students from SMP Negeri 15 Palu, 30 students from SMP Negeri 3 Palu, 30 students from SMP Negeri 10 Palu using Pretest-Posttest Control Group design. Research data collection was conducted using indirect interview techniques as a technique. The research data were analyzed by descriptive and inferential analysis (t-test). The results showed that: 1) the use of Banner media resulted in 40% of students increasing their discipline from low to moderate; 2) the use of X-Banner media resulted in 20% of students increased discipline from moderate to high, and 23.33% of students who increased their discipline from low to moderate; 3) the use of media Leaflets produced 13.33% of students who increased their discipline from being high, and 30% of students who increased their discipline from low to medium; 4) there is an influence on the use of Banner media in information services the impact of disciplinary violations on ked student discipline; 5) there is the influence of the use of X-Banner media in information services on the impact of disciplinary violations on student discipline; and 6) there is an influence of media use Leaflet in information services the impact of disciplinary violations on student discipline.